Effect of the Re-Vitrification of Embryos at Different Stages on Embryonic Developmental Potential - Li, Jingyu; Xiong, Shun; Zhao, Yanhua; Li, Chong; Han, Wei; Huang, Guoning (Frontiers in Endocrinology, 2021)
Background: Using re-vitrified human embryos for frozen-warmed embryo transfer (FET) is a valuable option when there are no other cryopreserved embryos to use, however, except for the PGT cases, no published data are available for FET with human embryos that were re-vitrified at different developmental stages. Objective: To evaluate the effect of re-vitrification of embryos at different stages on embryonic developmental potential. Method: This study included clinical retrospective and mouse experimental studies. For the retrospective study, a total of 25 FET cycles with re-vitrified day 3 embryos (re-vitrification group 1) and 54 FET cycles with re-vitrified day 5 blastocysts (re-vitrification group 2) between January 2015 and December 2019 were included in this study. The corresponding FET cycles with once-vitrified embryos were identified using propensity score (PS) matching according the time of embryo transfer. For the mouse experimental study, we divided embryos into 5 groups: fresh (group 1), vitrified at the 8-cell stage (group 2), vitrified at the early blastocyst stage (group 3), vitrified at the 8-cell stage , and re-vitrified at the 8-cell (group 4) or early blastocyst stage (group 5). The fresh embryos was selected as control group. The primary outcome in this study was delivery outcomes. Results: No significant difference in delivery rate was detected between re-vitrification group 1 (24.00%) and the corresponding control group (28.00%). However, re-vitrification group 2 (46.3%) showed a significant decrease in delivery rate compared with the two corresponding control groups (63.89% and 64.12%) (P < 0.05). Our experiment using mouse embryos also confirmed the clinical data, and showed that re-vitrification at the blastocyst stage following the first round of vitrification at the 8-cell stage reduced the delivery rate. In addition, both re-vitrified groups showed a significantly higher expression level of BAX. However, only re-vitrification at the blastocyst stage increased the expression level of CASPASE3. Conclusions: Re-vitrification at the 8-cell and blastocyst stages has different effects on embryonic developmental potential, as re-vitrification at blastocyst stage following a previous vitrification at 8-cell stage reduced the delivery rate, while vitrification at the 8-cell stage twice achieved comparable pregnancy outcomes to the once-vitrified group.